Animated Video Media in Guidance and Counseling Services: Innovations to Improve Student Learning Discipline - Wa Ode Husniah; Unhaluddin T Kurniawan; Sri Yuliandha (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2025)
Learning discipline is an important factor in students' academic success, but there are still many students who have difficulty maintaining it. This research aims to develop animated video-based guidance and counseling service media to improve students' learning discipline. The research and development (R&D) method was used with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects included media experts, material experts, and guidance and counseling teachers at SMP Negeri 4 Baubau. The data collection technique used a validation questionnaire with a Likert scale. The validation results show that the animated video media developed obtained a feasibility score of 77.5% from media experts and 85.12% from material experts, indicating that this media is very feasible to use in guidance and counseling services. This media is proven to help students understand the concept of learning discipline in a more interesting and interactive way, while increasing their involvement in the guidance and counseling service process. Therefore, the development of animated videos as a medium for guidance and counseling services can be an innovative solution in shaping students' study discipline habits and contributing to improving students' academic achievement.